Age of Drinking Initiation as a Risk Factor for Alcohol Use Disorder Symptoms is Moderated by ALDH2*2 and Ethnicity. (28th August 2017) - Luczak, Susan E.; Liang, Tiebing; Wall, Tamara L.
Abstract : Background: An early age of drinking initiation (ADI) has been associated with increased risk for alcohol use disorders (AUDs), but the consistency of this risk across diverse samples has not been well studied. The purpose of this study was to examine whether the pathway from ADI to AUD symptoms by early adulthood is moderated by ethnicity and possessing an alcohol‐metabolizing gene ALDH2*2 variant allele. Methods: We used multigroup structural equation modeling, including 5 groups split by ethnicity and ALDH2*2, to examine the consistency of the path from ADI to AUD symptoms in 604 Chinese‐, Korean‐, and White‐American college students. We further examined the effects of ALDH2*2, ethnicity, and their interaction in Asians to better understand their unique contributions to the moderation. Results: The association between ADI and AUD symptoms was moderated, with ADI negatively associated with AUD symptoms among Koreans without ALDH2*2 and Whites, but not among Koreans with ALDH2*2 or Chinese regardless of ALDH2*2 . Both ALDH2*2 and ethnicity within Asians contributed unique variability in the effect. Conclusions: Ethnicity and ALDH2*2 altered the relationship of ADI as a risk factor for AUD symptoms. Being Chinese and possessing an ALDH2*2 allele within Koreans both buffered against the risk for AUD symptoms associated with earlier ADI, indicating that this relationship can be attenuated by protective factors. Abstract : An early age of drinking initiation (ADI) has been associated with increased risk for alcohol use disorders (AUDs), but the consistency of this risk across diverse samples has not been well studied. We found both ethnicity (Chinese, Korean, White) and the alcohol metabolizing gene variant ALDH 2*2 moderated this relationship. Being Chinese and possessing an ALDH 2*2 allele within Koreans both buffered against the risk for AUD symptoms associated with earlier ADI, indicating that this relationship can be attenuated by protective factors.